Homing a Turkish Diaspora: Turkish American Women's Creative Labor - Reel Sen, Irem. (Tufts University. Tisch Library., 2019)
Homing a Turkish Diaspora: Turkish-American Women's Creative Labor In this dissertation, I study Turkish-American women's creative labor by interviews, surveys, and co-performance so that they can unearth their contributions, theorize their efforts, and insert themselves into dominant narratives. I analyze how Turkish-American women create multiple, conflicting, or complementary articulations of belonging through their representations. Through their embodied labor, I interpret global politics and racial attitudes surrounding their daily endeavors. My focus on performance also encourages a method of interview that allows people to articulate, document, and name their experiences. In each chapter, I focus on a different case study: stay-at-home-mom's food making; philanthropists' efforts to seek funding for projects back-home; dancers providing a specific Turkish image in a global, neoliberal economy. The growing interests in Middle Eastern Studies across the U.S. academy coincides with the U.S.'s fifteen-year efforts in the "war-on terror," and the desire to develop a greater understanding of the region. Middle Eastern diaspora in the U.S. serves as a fertile venue to study because it has its own imaginaries that are not in tune with those abroad. This global politics comes to bear on minoritarian subjects' daily endeavors. In this dissertation, I analyze how Turkish diaspora in Boston responds to political discourses surrounding the region, such as the U.S. war on terror and Turkey's secularization. How that diaspora responds to political discourses surrounding the region, as well as its religious make-up, points to multiple ideological contexts these diasporic bodies live in on a daily basis. They embody a racialization process that owes to Turkey's fraught place in the global political scene. Their daily performances point to the complex position Islam plays in the Turkish culture, emerging from a contentious history of secularization in Turkey, and their desire to protect against the growing Islamophobia in the U.S.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Drama.; Advisor: Kareem Khubchandani.; Committee: Noe Montez, Heather Nathans, and Claire Pamment.; Keywords: Gender studies, Theater, and Labor economics.